Approach‐oriented coping strategy level may be related to volume of the whole hippocampus in the elderly. Issue 4 (10th February 2020) - Kida, Hisashi; Nakajima, Shinichiro; Shikimoto, Ryo; Ochi, Ryo; Noda, Yoshihiro; Tsugawa, Sakiko; Fujii, Shinya; Takayama, Midori; Mimura, Masaru; Niimura, Hidehito
Abstract : Aim: Stress‐related disorders and severe stress exposure can cause atrophy of the whole hippocampus and its subfields. However, the impact of stress coping strategies on the hippocampus remains unclear. Therefore, we aimed to examine the relation between approach‐ and avoidance‐oriented coping strategies and hippocampal volume in elderly persons. Methods: A total of 1045 elderly persons living in Arakawa‐ward, Tokyo (mean ± SD age: 72.8 ± 5.2 years; 569 females [54.4%]) were included in the study and completed several questionnaires and face‐to‐face interviews and underwent magnetic resonance imaging. Approach‐ or avoidance‐oriented coping strategies were assessed with the Stress and Coping Inventory, while cognitive function and depressive symptoms were assessed with the Mini‐Mental State Examination and Geriatric Depression Scale, respectively. The volume of the whole hippocampus on T1‐weighted images was delineated and calculated using FreeSurfer 6.0. Multiple regression analyses were performed to examine the relation between Stress and Coping Inventory scores and whole hippocampal volume. Results: Approach‐oriented coping strategy scores were positively correlated with whole hippocampal volume. Furthermore, these relations remained significant after controlling for the influence of cognitive function and depressive symptoms on these volumetric variables. In contrast, avoidance‐oriented coping strategy scores were not correlated with whole hippocampal volume. Conclusion: This study demonstrated that hippocampal volume may be associated with the approach‐oriented coping strategy; therefore, this strategy may preserve hippocampal volume in the elderly.